Using phase change materials in photovoltaic systems for thermal regulation and electrical efficiency improvement: A review and outlook. (March 2015) - Ma, Tao; Yang, Hongxing; Zhang, Yinping; Lu, Lin; Wang, Xin
Abstract: The study presented in this paper is based on a detailed review of the literature focused on the use of phase change materials (PCM) for photovoltaic (PV) module thermal regulation and electrical efficiency improvement. The influence of high temperature on PV power generation has been examined and the findings have highlighted the importance of effective thermal regulation for PV models. Various PV cooling methods employed to maintain better PV performance are discussed and the recently emerging PV–PCM system concept for thermal regulation is introduced. A comprehensive literature review of the state-of-the-art aspects of this technology, such as system development, performance evaluation, materials selection, heat transfer improvement, numerical models, simulation, and application in practice is given. The PV–PCM system, however, might not be economically feasible if the enhancement of PV efficiency only is sought. The PV–ST–PCM system, i.e. integrated with a solar thermal (ST) system, has therefore been investigated as the stored heat can be extracted for other thermal applications. The dual PCM roles demonstrate significant application prospects for the combined technology. However, both PV–PCM and PV–ST–PCM systems are still mainly in the research and laboratory test stages, with obvious scope for practical applications but with attendant challenges. Suggestions for the future work are presented.